Analisis Pendekatan Pembelajaran Deep Learning Dalam Mendorong Kedisiplinan Siswa pada Pelajaran Pendidikan Pancasila di Kelas XA SMAN 10 Pontianak - Febrian Dwi Saputra; Nuraini Astriati; Shilmy Purnama; Bistari Bistari; Syamsuri Syamsuri (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
This research aims to analyze the application of the deep learning approach in encouraging student discipline in Pendidikan Pancasila lessons in class XA SMAN 10 Pontianak. The main problem addressed is low student discipline which impacts learning quality and character building. The research focus includes planning, implementation, and the contribution of the deep learning approach to the formation of student discipline. This study uses a qualitative approach with a descriptive method, where data were collected through observation, in-depth interviews, and documentation studies. The results indicate that lesson planning has systematically integrated the principles of mindful, meaningful, and joyful learning in the Deep Learning Lesson Plan (RPM). Lesson implementation was active, reflective, and contextual through discussions, two-way communication, and linking material with students' real-life experiences. The deep learning approach contributes positively to increasing student compliance with school rules, better learning time management, and the ability to accept sanctions reflectively. The discipline formed develops not through coercion, but as a form of self-awareness and intrinsic motivation in students. In conclusion, the deep learning approach is an effective strategy in forming student discipline character through meaningful, relevant, and joyful Pendidikan Pancasila learning.